MENINGKATKAN KEMAMPUAN MENGGUNAKAN CANGKANG KERANG MATERI SENI RUPA PADA SISWA KELAS V SDN 24 DUNGINGI - Shinta Oktavia; Wiwy Triyanty Pulukadang; Rustam I Husain; Rusmin Husain; Fidyawati Monoarfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of using seashells as a learning medium in improving the ability of fifth-grade students to create visual art at SDN 24 Dungingi, Gorontalo City. The main problem addressed in this research is the low level of students’ creativity and skills in producing art works. The research employed a Classroom Action Research (CAR) method conducted in two cycles, with data collection techniques including observation, interviews, documentation, and creativity tests. The research subjects were fifth-grade students of SDN 24 Dungingi. The results of the study indicate a significant improvement in students’ ability to create visual art after the implementation of seashell-based learning media. In the first cycle, 11 students achieved the Minimum Mastery Criteria (KKM), representing 59%. In the second cycle, the number increased to 18 students, equivalent to 95%. These findings suggest that the use of natural materials such as seashells provides contextual learning experiences, enhances students’ creativity, and encourages active participation in the learning process. Therefore, the use of seashells as a learning medium is proven to be effective in improving students’ learning outcomes in visual arts.